2020
DOI: 10.3846/jcem.2020.11659
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Procurement Irregularities in the Supply-Chain of Ghanaian Construction Projects: A Soft-Computing Approach

Abstract: This study examines procurement irregularities, as one of the most unexplored threats in the procurement process of construction projects. It also tests the suppositions associated with the contributions of irregularities to corruption in construction procurement. An expert survey is conducted with 62 construction-related practitioners selected via non-probabilistic sampling in the context of a Ghana, to assess the criticalities of the irregularities. Eighteen irregularities were identified within the context … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…Before moving towards the analysis of the results, Kaiser-Meyer-Olkin (KMO) was used to check the adequacy of data. Table 2 reveals that the KMO test value was 0.944, which is greater than the acceptable threshold 0.50; therefore, the sampling data is considered suitable for the explanatory factor analysis (Chan et al, 2011). Besides, Bartlett's test illustrated the level of significance to be 0.000, which is considered good as it is far below the 0.05 level of significance (refer to Table 2).…”
Section: Analytical Toolmentioning
confidence: 94%
“…Before moving towards the analysis of the results, Kaiser-Meyer-Olkin (KMO) was used to check the adequacy of data. Table 2 reveals that the KMO test value was 0.944, which is greater than the acceptable threshold 0.50; therefore, the sampling data is considered suitable for the explanatory factor analysis (Chan et al, 2011). Besides, Bartlett's test illustrated the level of significance to be 0.000, which is considered good as it is far below the 0.05 level of significance (refer to Table 2).…”
Section: Analytical Toolmentioning
confidence: 94%
“…Gou and Zhong (2019) diagnosed the fault degree of mechanical equipment, and the attribute set are the vibration amplitude at frequency at three frequencies and average amplitude of vibration displacement. Owusu et al (2020) identified the most critical procurement irregularity in construction project supply chain, and the evaluation criteria include contract monitoring irregularities, compliance irregularities, proceduralirregularities, and administrative-specific.…”
Section: Classification Of Multiple Criteria Decision Making Problems In Civil Engineeringmentioning
confidence: 99%
“…Next, the optimal facility management strategy was determined according to the performance index of facility management. Owusu et al (2020) identified the most critical procurement irregularity in construction project supply chain based on the fuzzy synthetic evaluation method. The questionnaire survey and snowballing methods were conducted to collect a list of criteria, and the mean index analysis was used to generate the relative importance of criteria.…”
Section: Individual Fuzzy Multiple Criteria Decision Making Modelsmentioning
confidence: 99%
“…Bid decision-making is essential to the business health of contractors, given that this is the main mechanism of allocating projects to contractors in the construction context (Asgari et al, 2016;Su et al, 2020). Despite such importance, a review run on the literature reveals major deficiencies and drawbacks in current bid decision-making practices of the construction industry (Owusu et al, 2020), as discussed below.…”
Section: Introductionmentioning
confidence: 99%